O direito fundamental da criança e do adolescente à integridade física: paradoxo à realidade do trabalho infanto-juvenil no município de João Pessoa-PB - Ribeiro, Glauco Ferreira de Souza (2008)
The Physical Exploration of children and adolescents like strength of work is essentially a chronic problem, gone by complex elements. Becomes object of attention of the society who see, in your reality, children exerting unhealthy occupations and dangerous, despite of all legislation of granted integral protection in the Brazilian right. In this direction, the coexistence between the exploration of childhood and adolescence together with the norms in the Brazilian legislative texts creates a true antagonism, guided for social, economic and cultural aspects. The general objective of the study consists of analyzes of the form which has been assured to the young the basic right to the physical integrity, tracing a theoretical and practical parallel between the guarantee of the norms and the reality of the exploration the one that many of them come being exposed like strength of work. The research has the methodology qualified in two aspects: with regard to the ends: It‟s explicative, because it looked to elucidate the factors that originate the physical exploration of children and adolescents like strength of work, as well as the main parameters of the public politics created to deal with the problematic one, glimpsed, over all, in the analysis of the reality lived for the small workers, evidenced in critical subtility. With regard to the means: bibliographical and of field. Bibliographical, because for the theoretical base, a deepened revision of literature concerning thematic of the children‟s work was made. This activity for what it looked to draw a short trajectory of the problem, including his principal characteristics and transformations, survived by the society along the history complemented by the analysis of the basic rights secured to the child and to the adolescent. In this direction, the Federal Constitution of 1988 is important. The investigation was also of field, because it disposed of the collection of data through interviews containing itineraries defined with hard-working children or in situations of risk in the city of João Pessoa PB. The analysis of the legislation shows that the Brazilian state has one of the most advanced legal systems of the world in which it refers to the protection of the physical entirety of the child and of an adolescent, but dissonant of the social reality of poverty, misery and exclusion survived by the children workers, suited the unemployment and the social, cultural and economical profile of the Brazilian society. There are not bases substantiated for criticism to the Brazilian legislation: his character of protection and respect to the peculiarities of the childhood and youth they are well-known and his inadequacy in front of the reality does not refer to his content, but his distance of this society marked by the inequality. Why does the legislation become really efficient, is it necessary to conjugate and to perfect efforts, since the law does not guarantee his fulfillment without a least integration between the society and the legislative and state-owned mechanisms that have the mission to face and to eradicate the children's work.